2022
DOI: 10.1177/00031348211069803
|View full text |Cite
|
Sign up to set email alerts
|

Naples Prognostic Score to Predict Postoperative Complications After Colectomy for Diverticulitis

Abstract: Background The Naples Prognostic Score (NPS) has proven efficacy as a prognostic tool for postoperative outcomes in patients undergoing surgery for neoplastic diseases. However, the role of the NPS score in inflammatory surgical diseases has not yet been studied. We aimed to evaluate NPS predictive value in patients undergoing colectomy due to diverticulitis. Methods A single-center retrospective study including all patients who underwent colectomy for diverticulitis between July 2008 and March 2020 was establ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 20 publications
(31 reference statements)
0
4
0
Order By: Relevance
“…Therefore, further investigation into the specific association between NPS and POD was warranted to enhance post-surgery patient outcomes. Additionally, while the optimal cut-off value of NPS had been extensively studied in the context of cancer survival [ 14 , 45 ]. Its exploration in predicting POD following gastrointestinal tumor surgery had been limited.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, further investigation into the specific association between NPS and POD was warranted to enhance post-surgery patient outcomes. Additionally, while the optimal cut-off value of NPS had been extensively studied in the context of cancer survival [ 14 , 45 ]. Its exploration in predicting POD following gastrointestinal tumor surgery had been limited.…”
Section: Discussionmentioning
confidence: 99%
“…Another article affirmed that preoperative NPS served as a robust prognostic factor in patients with ampullary cancer, demonstrating superior prognostic performance compared to other individual nutritional or inflammatory biomarkers [ 14 ]. Besides, the available evidence suggested that preoperative NPS was independently related to the prevalence of postoperative syndromes [ 15 ]. Despite this, there has been limited research on the role of NPS in predicting POD for the elderly with gastrointestinal tumors.…”
Section: Introductionmentioning
confidence: 99%
“…The NPS is a comprehensive measure of patients’ inflammation and nutritional status, consisting of serum albumin, total cholesterol, neutrophil/lymphocyte ratio (NLR), and lymphocyte/monocyte ratio (LMR). Studies have shown that it can accurately predict the prognosis of patients with myocardial infarction and congestive heart failure and identify malnutrition in hypertensive patients, acute renal failure following a myocardial infarction, and postoperative complications after diverticulitis [ 11 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Platelet‐to‐Lymphocyte Ratio (PLR) is one emerging marker, that was shown to be valuable in both inflammatory 8,9 and malignant 10–13 conditions. Its value increases when it is interpreted in combination with other markers, such as the Neutrophil‐to‐Lymphocyte Ratio (NLR)—another predictive marker used both individually and in combination with others 11,12,14–17 . The Lymphocyte‐to‐Monocyte Ratio (LMR) is a predictive marker that was shown to be useful mainly in malignant diseases, 18–20 and lately also in different bacterial infections 21,22 and other benign conditions such as osteoporosis 23 .…”
Section: Introductionmentioning
confidence: 99%
“…Its value increases when it is interpreted in combination with other markers, such as the Neutrophil-to-Lymphocyte Ratio (NLR)-another predictive marker used both individually and in combination with others. 11,12,[14][15][16][17] The Lymphocyte-to-Monocyte Ratio (LMR) is a predictive marker that was shown to be useful mainly in malignant diseases, [18][19][20] and lately also in different bacterial infections 21,22 and other benign conditions such as osteoporosis. 23 A prognostic score called the modified Systemic Inflammatory Score (mSIS) is based on LMR and serum albumin levels, that was also shown to be valuable in various malignant diseases [24][25][26] and is yet to be examined in benign conditions.…”
Section: Introductionmentioning
confidence: 99%